CORRELATION ANALYSIS OF ORIGINAL SCHOOL MAJOR, ACADEMIC ACHIEVEMENT, MAJOR CHOICE IN SPAN, UNIVERSITY STUDY PROGRAM, AND CUMULATIVE ACHIEVEMENT INDEX OF HIGH-ACHIEVING STUDENTS IN THE SPAN PROGRAM AT UIN MATARAM - Masnun; Fadli, Adi; Endrawati (Jurnal Tatsqif, 2025)
This study aims to analyze the relationship between the students' original school major, academic and non-academic achievements, choice of major through the National Academic Achievement Selection (SPAN) State Islamic Higher Education (PTKIN) pathway, the major pursued in higher education, and the Grade Point Average (GPA) of high-achieving students in the SPAN pathway at State Islamic University of Mataram (UIN Mataram). This study employs a quantitative correlational research design. The research location is at UIN Mataram with a sample size of 1,768 students accepted through the SPAN pathway. Data were collected through surveys and documentation of student academic records, including high school majors, academic/non-academic achievements, SPAN major choices, higher-education majors, and GPA. The research instruments were questionnaires and academic data documentation sheets sourced from official institutional archives. Data analysis techniques used Pearson Product-Moment correlation tests to determine the relationship between research variables. The results showed a positive and significant correlation between the major chosen in SPAN and the major taken at UIN Mataram, and a negative and significant correlation between the major at the university and the student's GPA. In addition, a significant negative correlation was found between the choice of major in SPAN and academic/non-academic achievement at the school of origin. Meanwhile, no significant relationships were found between the major in the school of origin and the major in college, the achievement in the school of origin, or GPA; likewise, no significant relationships were found between academic/non-academic achievement and GPA. The implications of this study indicate that students' academic success in higher education is not determined solely by their major and secondary education achievements, but is also influenced by the suitability of their major choice, program characteristics, and the learning context in higher education. These findings can inform the development of more comprehensive student selection policies and career guidance services that are aligned with students' interests and potential.